A standardized method to extract and store haemolymph from Apis mellifera and the ectoparasite Varroa destructor for protein analysis - Garrido, Paula Melisa (2013)
The ectoparasitic mite Varroa destructor is a serious problem for beekeeping. It sucks haemolymph from different stages of the bees causing significant damage (see review by Rosenkranz et al., 2010). Haemolymph collection from honey bees is required to perform immunological, physiological, nutritional and other assays. In the literature there are many dissimilar methodologies to extract and store haemolymph. The electrophoretic profile and protein contents of V. destructor have been little studied, but it is of great interest to evaluate the changes experienced by this tissue in response to different treatments in the host and its parasite. The aim of this study is therefore to propose a standard procedure for haemolymph collection and storage, extending previous studies and sharing our working experience.